Interactions II : - Pavlik, Cheryl (Tổng hợp Thành phố Hồ Chí Minh, 2007)
Lanugage proficiencies are articulated across five ability levels (beginning through advanced) within each of the four language skill strands. Chapter themes articulate across the four skill strands to systematically recycle content, vocabulary, and grammar.